2014
DOI: 10.1007/s00405-014-3323-9
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor (EGFR) expression in patients with laryngeal squamous cell carcinoma

Abstract: To assess the epidermal growth factor receptor (EGFR) correlation with histopathologic and clinical characteristics of laryngeal squamous cell carcinoma (SCC) and the impact of EGFR overexpression on patient survival. This retrospective study included 185 SCC patients treated at Clinical Department of ENT, Head and Neck Surgery, Split University Hospital Center between January 1, 2000 and December 31, 2009. A statistically significant correlation (p < 0.001) was recorded between the level of EGFR expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
4
5
0
1
Order By: Relevance
“…Therefore, the previous researches of VEGFR2 focused on its function of angiogenesis. However, our research revealed that VEGFR2 expressed strongly not only in the endothelial cells but also in tumor cells in HNSCC, which consisted with reports in other cancer (Guo et al, 2010;Silva et al, 2011;Mokhtari, 2012;Kontic et al, 2014). This result indicated thatVEGFR2 might play an important role inprogression of HNSCC.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the previous researches of VEGFR2 focused on its function of angiogenesis. However, our research revealed that VEGFR2 expressed strongly not only in the endothelial cells but also in tumor cells in HNSCC, which consisted with reports in other cancer (Guo et al, 2010;Silva et al, 2011;Mokhtari, 2012;Kontic et al, 2014). This result indicated thatVEGFR2 might play an important role inprogression of HNSCC.…”
Section: Discussionsupporting
confidence: 85%
“…The use of EGFR as a biomarker for response to EGFR inhibitor is limited by the semiquantitative nature of and subjectivity of immunohistochemical scoring 100102. It might be due to inaccurate assays as well as the nature of increased gene copy number being a less predictive biomarker compared to activating mutations 55.…”
Section: Introductionmentioning
confidence: 99%
“…In our protein analysis, overexpression of the marker was correlated with the grade of the examined cases. Another study has shown similar association combined, also, with overall advanced disease characteristics, including stage and metastasizing potential leading to poor prognosis (14). in vivo 33: 815-819 (2019) Interestingly, another study has concluded that the synergetic over activation of EGFR and hepatocyte growth factor tyrosine kinase receptor MET proto-oncogene, (c MET-gene locus: 7q31) is associated with poor survival especially in patients with glottis LSCC (15).…”
Section: Discussionmentioning
confidence: 91%